Defining an Intracellular Role of Hepatic Lipase in the Formation of Very Low Density Lipoproteins and High Density Lipoproteins - Bamji-Mirza, Michelle (Université d'Ottawa / University of Ottawa, 2011)
Hepatic lipase (HL) plays a pivotal role in the catabolism of apolipoprotein (apo)B-containing lipoproteins and high density lipoprotein (HDL) particles through its reported catalytic and non-catalytic extracellular functions. The current study tested the hypothesis that HL expression might impair formation and secretion of hepatic derived very low density lipoproteins (VLDL) and apoA-I (nascent HDL). Stable or transient expression of human HL (hHL) in McA-RH7777 cells resulted in decreased incorporation of [3H]glycerol into cell-associated and secreted (VLDL-associated) 3H-triacylglcyerol (TAG) relative to control cells. Stable expression of catalytically-inactive hHL (hHLSG) also resulted in decreased secretion of VLDL-associated 3H-TAG whereas cell-associated 3H-TAG levels were unchanged. Expression of hHL or hHLSG increased cell-associated 35S-apoB100 with relatively no change in secreted 35S-apoB100. Importantly, hHL or hHLSG expression resulted in reduced 3H-TAG associated with the microsomal lumen lipid droplets (LLD), and increased relative expression of ApoB and genes involved in lipogenesis and fatty acyl oxidation. Transient expression of hHL in HL-null primary hepatocytes, mediated by adenoviral gene transfer, resulted in decreased steady-state levels of cell-associated and secreted apoA-I and reduced rates of synthesis and secretion of 35S-apoA-I. HL-null hepatocytes exhibited increased levels of secreted 35S-apoA-I relative to wildtype hepatocytes while cell-associated 35S-apoA-I levels were normal. Transient expression of a hHL chimera (hHLmt), in which the C-terminus of hHL was replaced with mouse HL sequences, exerted an inhibitory effect on apoA-I production similar to that of hHL even though hHLmt was secreted less effectively than hHL with impaired exit from the endoplasmic reticulum (ER) as compared with hHL. In contrast, stable expression of hHL in McA-RH7777 cells resulted in a dose-dependent increase in cell-associated and secreted 35S-apoA-I levels. These studies demonstrate that hHL has an intracellular (but non-catalytic) role in reducing the content of the LLD and ultimately the buoyancy of secreted VLDL particles, and that the N-terminal sequences of ER-residing hHL directly or indirectly modulates the production and secretion of apoA-I (nascent HDL) from hepatocytes.
Keywords: apolipoprotein B-100; apolipoprotein A-I; heparan sulphate proteoglycans; lumenal lipid droplet